The influences of sustainability positioning on B2B brand loyalty in the manufacturing industry - Chan, Jerald Yew Loon (2023)
Many business-to-business [B2B] global firms today, are embracing sustainability stewardship as a form of competitive advantage and differentiation, and to enhance their corporate reputation. Evolving business landscape, stakeholders’ expectations, intensified competition for businesses and resources, increased customer demands for sustainability practices being more mainstream, are some of the other key reasons. However, in recent years, there is a weakening trend of sustainability reporting in some countries and their business leaders calling sustainability as “peripheral rather than a core issue”. As such, do business leaders in the manufacturing industry understand how their B2B customers perceive suppliers with weak [or superior] sustainability practices? And what about the real implications of poor sustainability performance from an industrial marketing perspective, for suppliers? Hence, in a nutshell, this study broadly aims to provide valuable and practical insights, for practitioners, managers, and industrial marketers, on how sustainability positioning could impact B2B firm’s branding performances. More specifically, the research framework aims to establish the relationship between factors of sustainability positioning with customer satisfaction and B2B brand loyalty, in the manufacturing industry. As a result, this study also academically contributes to the scarcity of industrial marketing literature and the literature gap on B2B sustainability positioning. This research looks through the lens and perception of B2B buyers, by utilizing a quantitative research design, whereby data are collected using an online questionnaire. The research findings indicated three factors of sustainability positioning that were significant predictors of customer satisfaction, and customer satisfaction was also significantly related to B2B brand loyalty, in the context of manufacturing industry. In addition, the discussion section examined B2B buyers’ perception on factors of sustainability positioning, customer satisfaction, and B2B brand loyalty. While the recommendation section analyzed the factors that selling firms or manufacturer need to consider for being perceived as a ‘sustainable superiority’ organization. Besides, the dissertation and study were extensively researched, and only credible sources, literature, and journals were reviewed. Finally, B2B firms need to comprehend that superior sustainability positioning is not impossible, and it can be accomplished more effectively and efficiently, with the insights in this research.